The pressure dependence of the decomposition temperature of methane hydrate in the presence of ammonia - Dr John Loveday; Dr Craig Bull; Dr Andreas Hermann; Mr Bernhard Massani; Professor Dr Kuhs; Dr Ciprian Pruteanu; Miss Katherine Brown (ISIS Facility, 2018)
The properties of methane ammonia water mixtures are crucial for models of how the outer planets evolved and yet have not been much studied. This proposal is for beamtime to measure the effect of ammonia on the decomposition of methane hydrates at high pressure.